The Determination of Acoustical Absorbing Materials in The “Al-Marwah” Room of “Al-Akbar” Mosque in Surabaya using Objective Parameters Approximation - Asmoro, Wiratno A. (IPTEK The Journal for Technology and Science, 2025)
The room that used to hold the speech activity needs a good acoustical quality. To determine the acoustical quality of a room the experimental research was conducted to find the relationship between the determination of acoustical absorbing materials and speech intelligibility in the “Al-Marwah” room of “Al-Akbar” mosque in Surabaya. Through the monaural acoustical measurements, the objective acoustical parameters in the “Al-Marwah” room can be found from impulse responses. Then we can use it to determine the acoustical absorbing materials in the room. Considering the acoustical parameters of RT, EDT, D50, C50, and percent Alcons at several positions, we can find the relationships between those parameters. The result, then, could be used to properly judge the acoustical absorbing materials which should be applied in the room. For the acoustical treatments on the ceiling of 376 square meters and the pillars of 373 square meters in the “Al-Marwah” room of the “Al-Akbar” mosque, the average values of RT and EDT on mid-band frequencies were found 5.52 seconds and 7.88 seconds respectively; whereas the values of D50, C50 and percent Alcons were found in the range of 3.25 to 10.5 percent, -15 to -9.4 decibels and 15 to 21 percent respectively. Those conditions produce speech intelligibility in Poor to Sufficient category.